The Koreas - Connor, Mary E. (Santa Barbara, Calif. : ABC-CLIO, 2009)
From the Publisher: Asia in Focus: The Korea's presents an authoritative and unprecedented look at the contrasts and similarities between the history, geography, politics, economy, culture, and society of North Korea and South Korea. It offers a wealth of new insights into North Korean life, as well as extensive explorations of Korean music, arts, language, cuisine, and popular culture, including the "Korean wave," which began with the export of Korean television dramas to other parts of Asia and has spread South Korean culture around the world. Also included are sections on women's history and roles, class and ethnicity, and a wide range of contemporary issues. For a deeper understanding of one of the most closely watched regions of the globe, this volume is a must.
Sadržaj: Preface -- Maps -- 1: Geography / Mary E Connor -- Korean Peninsula -- Physical geography: North Korea -- Physical geography: South Korea -- Human geography -- 2: History / Mary E Connor -- Early Korea -- Koryo dynasty (918-1392) -- Choson dynasty (1392-1910) -- Colonial period (1910-1945) -- Liberation, division, and the beginnings of the Cold War (1945-1950) -- Korean War (1950-1953) -- Divided Korea: the South Korean experience (1953-2008) -- Divided Korea: the North Korean experience (1953-2008) -- 3: Government And Politics / Mary E Connor -- Impact of tradition on political development -- Impact of the Japanese colonial period on contemporary life -- Impact on US and Soviet occupation and the Korean War on political development -- Divided people: South Korean experience (1948-2008) -- Divided people: North Korean experience (1948-2008) -- 4: Economy / Mary E Connor -- Economic development -- Industry -- Labor -- Trade -- 5: Society: Religion And Thought / Mary E Connor -- Introduction -- South Korea -- North Korea -- Social Classes And Ethnicity / Mary E Connor -- Early Korean history -- Three kingdoms period (57 BCE to 668 CE) -- Unified Silla (668-935 CE) -- Social classes during the Koryo dynasty (918-1392) -- Koryo society during the Yuan dynasty -- Choson dynasty (1392-1910) -- Later Choson dynasty: 1637-1910 -- Japanese colonial rule (1910-1945) -- Division and the Korean War (1945-1953) -- South Korea (1953-present) -- North Korea (1953-present) -- Conclusion -- Women And Marriage / Mary E Connor -- Three Kingdoms (57 BCE-668 CE) -- Unified Silla (668-935 CD) -- Koryo (918-1392) -- Choson dynasty (1392-1910) -- Opening of Korea and Japanese occupation (late 19th century-1945) -- South Korea (1945-present) -- North Korea (1945-present) -- Education / Mary E Connor -- Koryo -- Choson -- Japanese colonial period -- South Korea -- North Korea -- 6: Culture: Language / John Song -- Introduction -- History of Korean language -- Some major differences between Korean and Western languages -- Romanization of Korean -- Conclusion -- Etiquette / Mary E Connor -- Introduction: How not to succeed in Korea -- Confucian concepts and values -- How to succeed in Korea -- Literature / Bruce Fulton -- Introduction -- Three kingdoms -- Unified Silla -- Koryo -- Early Choson -- Later Choson -- Modern literature -- Literature in North Korea -- Recent developments -- Art And Architecture / Meher McArthur -- Introduction -- Prehistoric period -- Three Kingdoms period -- Unified Silla period (668-935) -- Koryo period (918-1392) -- Choson period (1392-1910) -- Modern period (1910- ) -- Music / Dong Suk Kim -- Introduction -- National music organizations -- History of traditional Korean music: ancient times to 1945 -- Characteristics if traditional music -- Contemporary music (1945-2008) -- Food / Mary E Connor -- Introduction -- Historical background -- Dietary customs -- Common Korean dishes -- Common beverages -- Ceremonial food: life's milestones -- Holiday festivals and food -- Leisure And Sports / Doug Kim -- South Korea: introduction -- Holidays and population migrations -- Traditional leisure -- Board and card games -- Games for girls and women -- Children's games -- Contemporary leisure -- Traditional sports -- Martial arts and martial sports -- Contemporary sports -- Participation in the Olympics -- Korean national sports festival -- Sports in North Korea -- 7: Contemporary Issues / Mary E Connor -- South Korea: the younger generation -- North Korea: the younger generation -- Korea's in the information era -- Korean wave -- United States and South Korea: are they drifting apart? -- Contemporary issues with ancient roots -- Glossary -- Facts and figures -- Holidays -- Organizations -- Annotated bibliography of recommended works on Korea -- Thematic Index -- Index.
Sadrži bibliografske bilješke i kazala.
Keywords: Južna Koreja -- kultura i civilizacija; Sjeverna Koreja -- kultura i civilizacija